The mechanism and pattern of injuries of undocumented immigrants crossing the Texas-Mexico border along the Rio Grande Valley - Carlos H. Palacio; Bianca Cruz; Cheryl Vanier; Jose Cano; Bradford G. Scott (BMC, 2021)
Abstract Background Apprehensions of undocumented immigrants in the Rio Grande Valley sector of the U.S.-Mexico border have grown to account for nearly half of all apprehensions at the border. The purpose of this study is to report the prevalence, mechanism, and pattern of traumatic injuries sustained by undocumented immigrants who crossed the U.S.-Mexico border at the Rio Grande Valley sector over a span of 5 years and were treated at a local American College of Surgeons verified Level II trauma center. Methods A retrospective chart review was conducted from January 2014 to December 2019. Demographics, comorbidities, injury severity score (ISS), mechanism of injury, anatomical part of the body affected, hospital and ICU length of stay (LOS), and treatment costs were analyzed. Descriptive statistics for demographics, injury location and cause, and temporal trends are reported. The impact of ISS or surgical intervention on hospital LOS was analyzed using an analysis of covariance (ANCOVA). Results Of 178 patients, 65.2% were male with an average age of 31 (range 0-67) years old and few comorbidities (88.8%) or social risk factors (86%). Patients most commonly sustained injuries secondary to a border fence-related incident (33.7%), fleeing (22.5%), or motor vehicle accident (16.9%). There were no clear temporal trends in the total number of patients injured, or in causes of injury, between 2014 and 2019. The majority of patients (60.7%) sustained extremity injuries, followed by spine injuries (20.2%). Border fence-related incidents and fleeing increased risk of extremity injuries (Odds ratio (OR) > 3; p < 0.005), whereas motor vehicle accidents increased risk of head and chest injuries (OR > 4; p < 0.004). Extremity injuries increased the odds (OR: 9.4, p < 0.001) that surgery would be required. Surgical intervention was common (64%), and the median LOS of patients who underwent surgery was 3 days more than those who did not (p < 0.001). Conclusion In addition to border fence related injuries, undocumented immigrants also sustained injuries while fleeing and in motor vehicle accidents, among others. Extremity injuries, which were more likely with border fence-related incidents, were the most common type. This type of injury often requires surgical intervention and, therefore, a longer hospital stay for severe injuries.